Predictor variables of addiction to training in Spanish master athletes - Antonio Zarauz Sancho; Francisco Ruiz-Juan (FEADEF, 2013)
In the last fifteen years has been in Spain a very significant increase in people over 35 years practicing Athletics at federative level. The aim of this study is to know their addiction to training and relationships with different variables of this training and athletic history. Also, get a sufficiently robust predictive models by sex, taking their addiction to these variables. Valuable descriptive data and training habits and athletic history were obtained, and that the addiction in Spanish master athletes have average levels, with the pleasure and relaxation subscale (positive and desirable) that obtains higher values, and abstinence and craving subscale (negative and undesirable) which gets lower. Both correlations as in the regression analysis, only one variant has been analyzed to be related or be predictive of addiction or any of its subscales. Due to these results it is necessary to further investigate this population in future research about your addiction to training including psychological variables as predictors of it (motivation, perception and beliefs about the causes of success, intrinsic satisfaction, etc.) to explainmore fully his addiction to training, especially in the case of men.